Structural testing of ungrouted post-tensioned cantilever masonry walls under unidirectional out-of-plane monotonic and cyclic loading. (15th May 2021) - García, John M.; Bonett, Ricardo L.; Schultz, Arturo E.
Highlights: Ungrouted post-tensioned masonry can be successfully implemented in cantilever retaining walls. Initial prestress is the main design parameter that influences the structural behavior of the retaining walls. The US and Canadian codes formulas provided the closest prediction of the experimental results. Abstract: Post-tensioning techniques improve the tensile strength of masonry substantially, endowing posttensioned masonry with performance comparable or superior to that of reinforced masonry cantilever walls. A useful structural application is for retaining walls, and although investigations have been made in posttensioned masonry cantilever walls, most of them focused on grouted elements and in-plane loads. This study investigated the influence of initial prestress and masonry strength in the behavior of ungrouted cantilever prestressed masonry walls with laterally unrestrained post-tensioned bars and which are intended as earth-retaining structures. The study also addresses the accuracy of different prestressed masonry code expressions to calculate the ultimate flexural capacity. The results show the ability of this structural system to withstand large lateral displacements with a limited and concentrated damage zone. The impact of masonry strength when the walls are loaded to ultimate conditions is less evident than that of initial prestress, and the USA and Canadian design code procedures show better correlation between numerical predictions and experimental data than do other worldwide codes.